2019
DOI: 10.1021/acsami.8b22343
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Biomimetic Gelatin–Gellan Gum Hydrogels for 3D Culture of Beating Human Cardiomyocytes

Abstract: To promote the transition of cell cultures from 2D to 3D, hydrogels are needed to biomimic the extracellular matrix (ECM). One potential material for this purpose is gellan gum (GG), a biocompatible and mechanically tunable hydrogel. However, GG alone does not provide attachment sites for cells to thrive in 3D. One option for biofunctionalization is the introduction of gelatin, a derivative of the abundant ECM protein collagen. Unfortunately, gelatin lacks cross-linking moieties, making the production of self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 69 publications
(192 reference statements)
3
47
0
Order By: Relevance
“…GEL can be blended with bio-informative materials that induce regular cell behavior. Koivisoto et al reported that functionalized GEL with gelatin could be the material for biomimicking scaffolds for 3D culture of human cardiomyocytes [17]. Because GEL does not provide attachment for cells, they chose the biofunctionalization of GEL with introduction of gelatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GEL can be blended with bio-informative materials that induce regular cell behavior. Koivisoto et al reported that functionalized GEL with gelatin could be the material for biomimicking scaffolds for 3D culture of human cardiomyocytes [17]. Because GEL does not provide attachment for cells, they chose the biofunctionalization of GEL with introduction of gelatin.…”
Section: Discussionmentioning
confidence: 99%
“…However, GEL, an anionic polysaccharide, can inhibit cell attachment [15]. By blending GEL with bio-informative materials, regular cell behavior can be induced [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, three‐dimensional (3D) cell culture in hydrogels offers stem cells a microenvironment mimicking the natural. Indeed, according to reports, collagen type I (COL) and polysaccharide gellan gum (GG) are besides biocompatible and bioresorbable hydrophilic natural polymer hydrogels, also suited to bone and vascularization applications (Gantar et al, ; Koivisto et al, ; Manda et al, ; Marelli et al, ; Oliveira, Custodio, Gasperini, Reis, & Mano, ). Also, injectable hydrogel biomaterials facilitate minimally invasive procedures thus avoiding risks of adverse complications (Kondiah et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A composite hydrogel with excellent biocompatibility prepared from KGM and carboxymethyl chitosan has been used as a wound dressing for wound healing [5]. In addition, blended polysaccharides have been used in intelligent hydrogels [6,7], aerogels [8], soil improvement [9], food moisture retention [10,11], and biological materials [12,13,14,15]. Studies on the interactions between polysaccharides have important practical application value.…”
Section: Introductionmentioning
confidence: 99%